Cities in the international marketplace : the political economy of urban development in North America and Western Europe - Savitch, H. V.; Kantor, Paul (Princeton : Princeton University Press, 2002)
It provides an innovative theory that explains how city governments bargain in the capital investment process to assert their influence.
Includes bibliographical references (p. [395]-424) and index.
uaj 27/02/2015
Loan
Keywords: Urban policy; Cities and towns; Cities and towns; Urban economics